Extra-Continental Migration and the Challenge of Development in Africa - Andza, Moses Saa-Aondo (Covenant University Journal of Politics and International Affairs, 2021)
This paper explores extra-continental emigration of Africans and the challenges it poses to the development of the African continent. The analytical research method was employed for the study and the Dependency Theory was espoused as a framework of analysis. The paper reveals that, though there is a 4.88 percent difference in favour of intracontinental migration of Africans, extra-continental emigration of Africans experiences stronger growth than the former. The study also finds extra-continental emigration of Africans culpable for the critically short supply of the core values of development on the African continent which have led to absolute underdevelopment of the continent. The paper establishes that, between 2011 and 2018, the African continent lost 17, 516 migrants at the Mediterranean Sea which is a direct cost to the development of Africa. Equally too, the African continent loses $2.0 billion annually, through extra-continental emigration of African professionals in the health sector alone, which is an indirect cost to the development of the continent. The paper also discovered that, remittances inflows in Africa have increased and it was projected that it would hit $85 billion in 2019. However, it cannot be compared to the direct and indirect cost of extra-continental emigration of Africans to the development of the continent. The paper concludes that, if the governments of the African continent do not address the phenomenon, it will further affect development. The paper recommends pragmatic leadership that will address the concerns that lead to extracontinental emigration of Africans.